Analisis Literasi Kesehatan dalam Buku Pelajaran Bahasa Indonesia Kelas XI SMA (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to describe the presentation and percentage of health literacy aspects in textbooks Indonesian grade XI high school. This research is qualitative descriptive research using content analysis methods. The data used is health literacy content in textbooks Indonesian grade XI high school. The data collection techniques used in this study were listening and note-taking techniques. Furthermore, the data analysis method used is a matching method using the Determining Element Sorting (PUP) technique with semantic and referential sorting methods. The data validity technique used is triangulation of theory with confidence levels through persistence and observation techniques. The results of the analysis showed that aspects of health literacy presented in textbooks Indonesian grade XI SMA consisted of aspects of food and drink, physical activity, physical violence/injury, sexual behavior, mental health, protective factors, environmental hygiene, hair hygiene, cigarette consumption, and illegal drug consumption. The lowest health literacy presentation is found in e-books Indonesian grade XI SMA (published by the Ministry of Education and Culture); That's 35% (enough). Next, health literacy in the "Pride of My Indonesian Nation" from the Triad is expressed in percentage 30% (sufficient). While the "Indonesian" of Yrama Widya is calculated at 36% (sufficient). The highest presentation of health literacy aspects in textbooks is the protective factor aspect with a percentage of 37% which is included in the sufficient category of the overall data